RGB imaging for monitoring quality parameters of sweet potato during drying - Onwude, D.I.; Hashim, N.; Abdan, K.; Janius, R.; Che Adan, S.N.; Jalaluddin, A. (International Society for Horticultural SciencePastoriestraatBierbeek3360info@ishs.org, 2020)
This study investigated the potential of using RGB imaging for monitoring the quality attributes of sweet potato during drying. Digital images of sweet potatoes were captured after every 1 h of drying at drying temperatures of 50-70°C and slice thickness of 4 mm, respectively. Similarly, reference properties of moisture content and color coordinates were measured after every 1 h under the same drying conditions using conventional methods. It was observed that there were strong correlations between the RGB parameters and the measured quality properties. RGB parameter showed good correlation with the change of moisture content, L* and a* color properties of sweet potato for all drying conditions with R2>0.5. Thus, this study has shown that RGB imaging can serve as a non-destructive tool for detecting the changes in quality of agricultural product during drying.